Islamic Financial Integration: The Operational Integration Dimension of Indonesian Students Business Activities at Al-Azhar University Cairo - Muhammad, Hafiz Akbar; Indra (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This study aims to analyze the factors influencing the intention of Indonesian students at Al-Azhar University, Cairo, to implement the operational integration of Islamic social and commercial finance in their entrepreneurial ventures. Holistic Islamic finance encompasses both social (zakat, infaq, waqf, and microfinance) and commercial aspects; however, integrating these components operationally remains a challenge. This research examines the influence of five variables—religiosity, knowledge, attitude, functional factors, and trust—on the intention to operationally integrate Islamic finance. Methodology – A quantitative approach was employed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The study sample comprised 91 Indonesian students at Al-Azhar University who are engaged in business activities. The findings reveal that four variables—attitude, religiosity, knowledge, and trust—have a significant positive effect on the intention to integrate Islamic finance, whereas functional factors do not exhibit a significant influence. This study contributes theoretically by extending the Theory of Planned Behaviour (TPB) within the context of Islamic finance, and practically by informing strategies to enhance student participation in Islamic finance integration. Findings – These findings can also serve as a foundation for developing policies aimed at strengthening the role of Islamic financial institutions in supporting sustainable social-commercial integration. The study provides both theoretical contributions, through the expansion of the TPB model in the Islamic finance context, and practical contributions, by offering insights into strategic efforts to increase student involvement in the integration of Islamic finance. Keywords: Islamic Financial Integration, Intention, Religiosity, Theory of Planned Behaviour, Al-Azhar Students, PLS-SEM